PUBLIC PROTECTION AND DISASTER RELIEF SEBAGAI KERJASAMA PENGELOLAAN BENCANA KAWASAN ASIA-PASIFIK DAN SOFT-POWER DIPLOMACY: STUDI KOMPARATIF TIONGKOK-INDONESIA - Riqian Ayu Dyah Apsari, (2020)
Public Protection and Disaster Relief (PPDR) is an innovative Information, Communications, and Technology way to develop regional disaster management in Asia-Pacific where each country in the region develop their PPDR, particularly China and Indonesia. PPDR development in Indonesia should be the country's chance to fix its Early Warning System and soft-power diplomacy as potential capability. This study is a qualitative research using semi-structured interview and literature review as the methods. The comparative case used in this study are Sichuan Earthquake and Sunda Strait Tsunami. This study found that PPDR in Indonesia should fix the country's Early Warning System and this development turned out to need corporate social responsibility from big telecommunication companies. Meanwhile in China, PPDR could make the country's disaster managemen more efficient and it is found that big telecommunication company from China was a part of PPDR development in Indonesia. More from that, PPDR development could become country's potential to address their soft-power diplomacy. It is applied to both China and Indonesia, based on fact that PPDR is a way to harmonize commercial and disaster communications technology. It is found that Indonesia is not far away from China for its digital connectivity based on Global System for Mobile Telecommunication (GSMA). A channel is open to both countries to address their means to collaborate or open up a corperation as well in the so called Asia-Pacific Telecommunity, where Indonesia and China both members of that institution. Finally, this study is a comparison between China and Indonesia in developing their PPDR as a corperation in the region and each countries potential to address soft-power diplomacy. So that, Indonesia especially, can get the lesson from the comparison.